2014
DOI: 10.1517/13543784.2015.993753
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of PD0332991 (Palbociclib) in the treatment of multiple myeloma

Abstract: While PD0332991 is essentially cytostatic, inducing prolonged G1 arrest, it enhances the cytotoxic effect of other agents effective in MM, including bortezomib and lenalidomide, as confirmed in early phase clinical trials. However, with a plethora of other drugs of different classes being tested in MM, further development of PD0332991 will depend on defining the most efficacious combination with least toxicity. An unexplored opportunity remains the potential protective effect of PD0332991 against lytic bone le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Indeed, pretreatment with highly selective CDK4/6 inhibitors (PD-0332991 or 2BrIC) increased radioresistance of RB1-positive melanoma cells and immortalized fibroblasts [ 139 ], whereas combination treatments with radiation administered either concurrently or sequentially with PD-0332991 resulted in increased anticancer activity in mice with RB1-positive glioblastoma intracranial xenografts [ 140 ]. Moreover, PD-0332991 sensitized myeloma cells to cell death induced by different cytotoxic agents, such as the glucocorticoid dexamethasone, the proteasome inhibitor bortezomib and the immunomodulatory agent lenalidomide, as indicated by both preclinical studies and clinical trials [ 138 , 142 144 ]. Therefore, a thorough understanding of the effects of CDK4/6 inhibition in combination with different cytotoxic agents is required to define the best treatment schedule in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, pretreatment with highly selective CDK4/6 inhibitors (PD-0332991 or 2BrIC) increased radioresistance of RB1-positive melanoma cells and immortalized fibroblasts [ 139 ], whereas combination treatments with radiation administered either concurrently or sequentially with PD-0332991 resulted in increased anticancer activity in mice with RB1-positive glioblastoma intracranial xenografts [ 140 ]. Moreover, PD-0332991 sensitized myeloma cells to cell death induced by different cytotoxic agents, such as the glucocorticoid dexamethasone, the proteasome inhibitor bortezomib and the immunomodulatory agent lenalidomide, as indicated by both preclinical studies and clinical trials [ 138 , 142 144 ]. Therefore, a thorough understanding of the effects of CDK4/6 inhibition in combination with different cytotoxic agents is required to define the best treatment schedule in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Given the effectiveness of this drug demonstrated by many studies, its use is likely to increase in the coming years. In addition, new therapeutic indications are emerging: multiple myeloma treatment [4] and intracranial growing teratoma syndrome [5], which suggests a possible increase in the frequency of its adverse effects. In this scenario, oral surgeons must be made aware of its side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that EPA and DHA can inhibit cell proliferation and induce apoptosis of MDA-MB-231 human breast cancer cells through the incorporation of these fatty acids into lipid rafts, leading to an activation of p38MAPK and a decrease in EGFR levels in lipid rafts in spite of the accompanied phosphorylation of EGFR [74]. Moreover, both EPA and DHA can reduce surface expression of CXCR4, leading to a decrease of CXCR4-mediated cell migration of MDA-MB-231 cells [75]. These studies have provided evidence that omega-3 polyunsaturated fatty acids can modify lipid raft in both biochemical and biophysical features, decreasing the content of cholesterol and distribution of key proteins [76].…”
Section: Anticancer Strategies By Using Cholesterol-depleting or Lipimentioning
confidence: 99%